Whole slide histologic grading of breast cancer using convolutional neural networks. - Demir, Gokhan; Iheme, Leonard O.; Solmaz, Gizem; Yazici, Cisem; Tokat, Fatma; Cayor, Sercan; Bozaba, Engin; Tekin, Muhammet Eren; Ozsoy, Gülsah; Ayalto, Samet; Kayhan, Cavit Kerem; Ince, Umit; et al. (LIPPINCOTT WILLIAMS \& WILKINS, 2022)
Annual Meeting of the American-Society-of-Clinical-Oncology (ASCO), ELECTR NETWORK, JUN 03-07, 2022